Implementasi Sistem Keuangan Desa dalam Meningkatkan Efisiensi dan Transparansi Pengelolaan Keuangan Nagari di Kecamatan Harau Kabupaten Lima Puluh Kota - Benita Valah; Rotzami Rotzami; Ardieansyah Ardieansyah (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This research aims to analyze the implementation of the village financial management system in an effort to improve the efficiency and transparency of nagari financial management in Harau District, Lima Puluh Kota Regency. The village financial system is an important instrument in the financial governance of village or nagari governments, supporting accountability, efficiency, and transparency. Using a descriptive qualitative approach, this study collects data through in-depth interviews, observation, and documentation studies in five nagari in Harau District. The results show that the implementation of the village financial system has brought significant changes in increasing the efficiency of budget management and the transparency of financial reporting. Several supporting factors for the successful implementation have been identified, including the commitment of nagari leaders, adequate human resource capacity, and support from information technology infrastructure. However, some challenges remain, such as the limited expertise of nagari officials in operating the system and uneven internet connectivity. This research recommends strengthening the capacity of nagari officials through ongoing training, providing adequate information technology infrastructure, and developing a more comprehensive monitoring and evaluation system.